Stochastic Model of Pneumonia and Meningitis Co-infection Using Continuous Time Markov Chain Approach - Anggun Praptaningsih; Hadi Sumarno; Paian Sianturi (Jurnal Penelitian Pendidikan IPA, 2023)
Pneumonia disease is a lung infection caused by Streptococcus pneumoniae. Meningitis is an infection of the meninges and cerebrospinal fluid caused by Streptococcus pneumoniae. Both diseases may occur at the same time. A mathematical model is needed to represent the spread of pneumonia and meningitis co-infection. This study aims to build the stochastic model of pneumonia and meningitis co-infection with CTMC, determine the transition and outbreak probability, and conduct simulations to assess the effect of increasing the contact rate on pneumonia  and meningitis . Based on the computer simulation undertaken, it can be concluded that if  was decreased while was set to be fixed, the probability of disease outbreak decreased.  If was set to be fixed while  was decreased, the probability of disease outbreak decreased. However, the latter is smaller than the previous. Similarly, if  was increased while was set to be fixed, the probability of disease outbreak increased.  If was set to be fixed while  was increased, the probability of disease outbreak increased. However, the latter is smaller than the previous. Moreover, if both  and  were decreased, the probability of disease outbreak was equal to zero.